Optimised sight adjustment processes for archers - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
During an archery competition, archers frequently fail to correctly adjust their bow`s sight so that their arrow groups are centred on the target. Arrows are shot in ends of three or six, depending on the phase of the competition, and consequently each end provides very limited data on which to make sight adjustments, although at the conclusion of the competition it is usually obvious if an archer has succeeded in the task or not. This paper considers three sight optimisation processes with a view to minimise score loss both in ranking rounds and in matches. It is shown that archers should take a more aggressive rather than a less aggressive approach to sight movements, especially for the first end. Each sight adjustment process can be implemented using a simple look-up table.